THE WAYS OF INCREASING OF QUALITY AND ACCESSIBILITY OF PEDIATRIC MEDICAL SERVICE IN OUT-PATIENT CLINICS - A.A. Baranov; A.G. Il'in; S.R. Konova; E.V. Antonova ("Paediatrician" Publishers LLC, 2009)
The analysis of dynamics of official statistics rates (population size, morbidity, disability, and mortality), and results of special scientific studies (morbidity, physical development), make it possible to show basic tendencies of children's health state changes in modern conditions. The result of pediatrists from out-patient clinics survey, questioning of parents and adolescents (12-17 years old), on the problem of children's health service, are presented. Questionnaire poll was held in regions of Central, Privolzhskiy, and Siberian Federal Districts. The complex analysis of obtained results show low quality level and accessibility of prophylactic and treatment medical service in children. This data became the basis of main directions of work of controlling and public health service in the field of increasing of quality and accessibility of pediatric medical service in out-patient clinics.Key words: children, medical service, out-patient clinics, quality, accessibility.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):5-9)